Post Brexit crystal ball gazing: What the future holds for Phase I Clinical Trials in the UK. (September 2016) - Matthews, Gene; Williams, Nancy
EU Regulation 536/2014 ("Regulations") is due to take practical effect across the Eurozone by the end of 2017 at the earliest and no later than October 2018 following the implementation of procedural requirements. It will replace the EU Clinical Trials Directive 2001/20/EC. The Regulations are designed to reverse what regulators described as a downward trend in the conduct of clinical trials within Europe because of the "lengthy and cumbersome application process and the failure of the pre-existing regime to accommodate the global scope of clinical trials." The purpose of the Regulations is to simplify and harmonise the administrative provisions governing clinical trials in the EU. With pleasing Pharmaceutical companies high on the political agenda, the pertinent question that arises is whether patient and public interests will be overlooked to cater to industry concerns? This article will outline the changes effected by the Regulation. It will evaluate the impact these changes will have on patient safety in the context of Phase I or First-in-human (FIH) trials by examining the TGN1412 clinical drug trial (also known as the Northwick Park drug trial). The second part of this article will discuss whether there is a place for the Regulations in the post Brexit landscape. The continuing uncertainty surrounding Brexit means that it remains difficult to come to any definitive conclusions but there are significant issues that require closer examination at this time.